Renewable energy : in the context of Turkey’s energy policy with special reference to the EU policies - Şekercioğlu, Selma (My University, 2011)
Yenilenebilir enerji, Dünya sistemindeki gelişmelere paralel olarak 1970’lerden sonra önem kazanmaya başlamıştır. Fakat hem AB’de hem de Türkiye’de yenilenebilir enerji politikalarının inşası milenyum sonrasında hızlanmıştır. Yenilenebilir enerji politikasını AB ile karşılaştırmalı olarak inceleyebilmek için tarihsel süreçlere bakmak gerekmektedir. Bu tarihsel süreçte karar alma stilleri ile ilgili bir takım sorunların mevcut olduğu görülmektedir. Bu sorunlar AB için Birlik yapısıyla ilgiliyken, Türkiye’nin yaşadığı güçlükler mali ve teknik problemlerden kaynaklanmaktadır. 2000’lerden sonra yenilenebilir enerji politikalarında iyi bir ilerleme gözükse de Türkiye için mevcut politikalar etkili bir strateji oluşturmak için yeterli değildir. Dahası mevcut destek mekanizmaları yenilenebilir enerji yatırımlarını desteklemek için yeterli değildir. Farklı kategorilerden farklı aktörlerin katılımıyla gerçekleşecek iyi tasarlanmış ve kapsamlı enerji politikasının inşa edilmesine gerek vardır. Bu çerçevede Türkiye’nin yenilenebilir enerji politikasının gelecek kestirimi perspektifi ile değerlendirilmesi gerekmektedir. Yenilenebilir enerji politikası, AB, Türkiye

Renewable energy has started to gain importance after the 1970’s in parallel with the developments in the World system. But the construction of renewable energy policies both in the EU and Turkey has accelerated after the millennium. In order to examine Turkey’s renewable energy policy in comparison with the EU policies, it is necessary to look at their historical processes. In this historical process it has been seen that there were some problems about decision making styles. For Turkey the difficulties arise from the fiscal and technical problems whilst in the EU the problems were related with the Union structure. After 2000’s there was a good progress in renewable energy policies but for Turkey the existing policies are not sufficient enough to have an efficient strategy. Moreover the existing support mechanisms are not enough to urge the renewable energy investments. There is a need for constructing a well designed and comprehensive energy policy with the involvement of different actors from different categories. From this framework, it is a necessity to assess Turkey’s renewable energy policy with its future projection perspective. Renewable energy policy, the EU, Turkey
Keywords: Avrupa Birliği_Türkiye; Yenilenebilir Enerji Politikası